2023
DOI: 10.3389/fimmu.2023.1237986
|View full text |Cite
|
Sign up to set email alerts
|

Use of high-plex data provides novel insights into the temporal artery processes of giant cell arteritis

Simon Parreau,
Elsa Molina,
Stéphanie Dumonteil
et al.

Abstract: ObjectiveTo identify the key coding genes underlying the biomarkers and pathways associated with giant cell arteritis (GCA), we performed an in situ spatial profiling of molecules involved in the temporal arteries of GCA patients and controls. Furthermore, we performed pharmacogenomic network analysis to identify potential treatment targets.MethodsUsing human formalin-fixed paraffin-embedded temporal artery biopsy samples (GCA, n = 9; controls, n = 7), we performed a whole transcriptome analysis using the Nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In a recent study using spatial transcriptomics, CD74 (HLA class-II histocompatibility antigen) was identified as the most differentially expressed gene across all arterial compartments between GCA-arteries (n=9) and controls (n=7). 114 Additionally, immunofluorescence staining showed CD74 to colocalise with the fibroblast marker CD90 in the media-intima border. 114 Greigert et al also demonstrated that myofibroblasts significantly expressed HLA-DR, compared with controls.…”
Section: Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent study using spatial transcriptomics, CD74 (HLA class-II histocompatibility antigen) was identified as the most differentially expressed gene across all arterial compartments between GCA-arteries (n=9) and controls (n=7). 114 Additionally, immunofluorescence staining showed CD74 to colocalise with the fibroblast marker CD90 in the media-intima border. 114 Greigert et al also demonstrated that myofibroblasts significantly expressed HLA-DR, compared with controls.…”
Section: Reviewmentioning
confidence: 98%
“…114 Additionally, immunofluorescence staining showed CD74 to colocalise with the fibroblast marker CD90 in the media-intima border. 114 Greigert et al also demonstrated that myofibroblasts significantly expressed HLA-DR, compared with controls. 23 Stromal cells can express MHC class II molecules in response to inflammatory stimuli 115 116 ; however, whether they have the capacity to induce T-cell proliferation analogous to conventional antigen-presenting cells remains unclear.…”
Section: Reviewmentioning
confidence: 98%
“…Over 12000 genes were found to be upregulated in the arteries, with differential expression according to different arterial layers. Interestingly, the immune-related functions and vascular remodeling were limited to the intima and media (26). A genetic approach was also used to estimate the proportion of misdiagnosis in patients with a clinically confirmed diagnosis of GCA, not supported by TAB or imaging.…”
Section: Biomarkers and Implications In Thepathogenesismentioning
confidence: 99%